Socio-Economic Status of Cotton Growers in Western Zone of Punjab, India - Lovpreet Kaur; Sunish Sharma (Archives of Current Research International, 2025)
Cotton is one of the major cash crops of western zone of Punjab. Multistage purposive cum random sampling technique was used for the selection of the study area. The present study on socio-economic status of cotton growers of Bathinda and Mansa districts of Punjab was carried on limited number of farmers in year 2023-24. The study was taken up in Maur and Mansa blocks from Bathinda and Mansa districts respectively with a sample size of 120 respondents. The farmers interviewed personally by a well-structured interview schedule. The data was coded, tabulated and analysed using suitable statistical tools. The profile of the cotton growers’ reveals that majority of them were middle aged, educated up to high school and senior secondary, had 4 to 10 ha of land holdings, more area under cotton, more participation of women than men, more farming experience and had own implements of farming. The study may prove beneficial to the policy makers and stakeholders in decision making and agricultural development.